Soviet-Chinese Relations, 1945-1970 - Koloskov, B. T. (Indiana University Press, 1975)
Soviet-Chinese Relations, 1945-1970 is the only book-length acount of Sino-Soviet relations between 1945 and 1970 in any language. Written by two Soviet experts on China on the basis of extensive research in secret party and government archives, it is the officially authorized Soviet version of the conflict, in effect a primary source of major significance, constantly quoted as such by Soviet specialists in modern history and international relations. This study both incorporates and reflects the current Soviet policies and attitudes roward the Maoist leadership in Peking; it also enables the reader to project Soviet actions and reactions into the future.